Defining significant childhood illness and injury in the Emergency Department: a consensus of UK and Ireland expert opinion - Lillitos,PJ; Lyttle,MD; Roland,D; Powell,CVE; Sandell,J; Rowland,AG; Chapman,SM; Maconochie,IK (Emergency Medicine Journal, 2018)
Background Clarifying whether paediatric early warning scores (PEWS) accurately predict significant illness is a research priority for UK and Ireland paediatric emergency medicine (EM). However, a standardised list of significant conditions to benchmark these scores does not exist.Objectives To establish standardised significant illness endpoints for use in determining the performance accuracy of PEWS and safety systems in emergency departments (ED), using a consensus of expert opinion in the UK and Ireland.Design Between July 2017 and February 2018, three online Delphi rounds established a consensus on ‘significant’ clinical conditions, derived from a list of common childhood illness/injury ED presentations. Conditions warranting acute hospital admission in the opinion of the respondent were defined as ‘significant’, using a 5-point Likert scale. The consensus was a priori ≥80% (positive or negative). 258 clinical conditions were tested.Participants and settings Eligible participants were consultants in acute or EM paediatrics, or adult EM, accessed via 53 PERUKI (Paediatric Emergency Research in the UK and Ireland)’s research collaborative sites, and 27 GAPRUKI (General and Adolescent Paediatric Research in the UK and Ireland)’s sites, 17 of which overlap with PERUKI.Main outcome measures To create a list of conditions regarded as ‘significant’with ≥80% expert consensus.Results 43 (68%) of 63 PERUKI and GAPRUKI sites responded; 295 experts were invited to participate. Participants in rounds 1, 2 and 3 were 223 (76%), 177 (60%) and 148 (50%), respectively; 154 conditions reached positive consensus as ‘significant’; 1 condition reached a negative consensus (uncomplicated Henoch-Schönlein purpura); and 37 conditions achieved non-consensus.Conclusions A list of significant childhood conditions has been created using UK and Irish expert consensus, for research purposes, for the first time. Th